IMPLEMENTATION OF THE DIJKSTRA ALGORITHM IN FINDING THE SHORTEST ROUTE TO AL-AZIZIYAH ISLAMIC BOARDING SCHOOL – LDII IN SAMARINDA - Chandra Nugraha; Delvina tri agustin; arif Budiarto (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2022)
Globalization Technology is growing very rapidly uncontrollably, the ease of use of technology is supported by the many emerging technology tools that are very easy to obtain, even some technology tools sold at very affordable prices. Android technology installed and packed in the form of smartphones is familiar to use even among people who are marginalized in the corners of the region. Not only are the intellect literate with technology utilizing the ease and development of this technology, even the lay people who utilize the internet network and are familiar with google can also mark the location of its place on google maps. With the globalization of this technology, the author will use the Implementation of Alghorithm Dijkstra In Finding the Shortest Route from the author's residence to Al-Aziziyah Islamic Boarding School – Ldii Di Samarinda. In this study, algorithm Dijkstra used alghorithm in determining the shortest path from the starting point to the destination point in a graff or shortest path with the help of LBS (Location Based Service), GPS, Google Maps, and Graff then found the shortest path was 4.88 km.